Synergistic targeting and resistance to PARP inhibition in DNA damage repair-deficient pancreatic cancer. Issue 4 (1st September 2020) - Gout, Johann; Perkhofer, Lukas; Morawe, Mareen; Arnold, Frank; Ihle, Michaela; Biber, Stephanie; Lange, Sebastian; Roger, Elodie; Kraus, Johann M; Stifter, Katja; Hahn, Stephan A; Zamperone, Andrea; et al.
Abstract : Objective: ATM serine/threonine kinase (ATM) is the most frequently mutated DNA damage response gene, involved in homologous recombination (HR), in pancreatic ductal adenocarcinoma (PDAC). Design: Combinational synergy screening was performed to endeavour a genotype-tailored targeted therapy. Results: Synergy was found on inhibition of PARP, ATR and DNA-PKcs (PAD) leading to synthetic lethality in ATM-deficient murine and human PDAC. Mechanistically, PAD-induced PARP trapping, replication fork stalling and mitosis defects leading to P53-mediated apoptosis. Most importantly, chemical inhibition of ATM sensitises human PDAC cells toward PAD with long-term tumour control in vivo. Finally, we anticipated and elucidated PARP inhibitor resistance within the ATM-null background via whole exome sequencing. Arising cells were aneuploid, underwent epithelial-mesenchymal-transition and acquired multidrug resistance (MDR) due to upregulation of drug transporters and a bypass within the DNA repair machinery. These functional observations were mirrored in copy number variations affecting a region on chromosome 5 comprising several of the upregulated MDR genes. Using these findings, we ultimately propose alternative strategies to overcome the resistance. Conclusion: Analysis of the molecular susceptibilities triggered by ATM deficiency in PDAC allow elaboration of an efficient mutation-specific combinational therapeutic approach that can be also implemented in a genotype-independent manner by ATM inhibition.